Using PhonBank and Phon in studies of phonological development and disorders. - Rose, Yvan; Stoel-Gammon, Carol (Clinical Linguistics & Phonetics)
The goal of this paper is to present an overview of new tools that can be used to further our understanding of phonological development and disorders. We begin with a summary of the field of child phonology with a focus on databases and methods of analysis and then move to a description of PhonBank, a shared database for the study of phonology, and Phon, a specialised software system capable of performing various types of phonological analyses based on both phonetic transcriptions and acoustic analyses of speech productions. We provide a detailed example of using PhonBank and Phon to examine the use of velar fronting using longitudinal data from one child with typical development and three children with phonological disorder. We conclude with an emphasis on data sharing and its central relevance to further advances in our field.